Four Polymorphs of the Bioactive Diuretic Drug 4-Chloro-5-chlorosulfonyl Salicylic Acid - Maria Olimpia Miclaus; Gheorghe Borodi; Alexandru Turza (Crystals)
4-chloro-5-chlorosulfonyl salicylic acid [C7H4Cl2O5S] is a derivative of salicylic acid and a diuretic agent. Its ability to form polymorphs through recrystallization from various solvents was demonstrated. As a result, four polymorphs were successfully obtained and analyzed using single-crystal X-ray diffraction and powder X-ray diffraction, which represents a novelty regarding the polymorphism of this compound of pharmaceutical interest. The solid-state properties were investigated by evaluating crystal lattice energies and intermolecular interactions.